The Interplay of Personal Branding and Emotional Labor in Shaping Employee Engagement - Ega Leovani; Florentinus Heru Ismadi (Jurnal Ragam Pengabdian, 2026)
Employee engagement remains a challenge in frontline service work characterized by high emotional demands. Drawing on Job Demands–Resources Theory, this study examines the relationships between personal branding, emotional labor, and employee engagement among beauty advisors in the cosmetics retail sector. A cross-sectional survey was conducted and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that personal branding positively influences emotional labor, while emotional labor has a strong positive effect on employee engagement. Emotional labor was found to fully mediate the relationship between personal branding and employee engagement, highlighting emotional regulation as a key mechanism linking professional identity to engagement in frontline service roles. The findings contribute to engagement literature by positioning personal branding as a relevant personal resource and by demonstrating the supportive role of emotional labor in sustaining employee engagement.